2009
DOI: 10.1158/1078-0432.ccr-09-0089
|View full text |Cite
|
Sign up to set email alerts
|

EGFR/KRAS/BRAF Mutations in Primary Lung Adenocarcinomas and Corresponding Locoregional Lymph Node Metastases

Abstract: Purpose: The epidermal growth factor receptor (EGFR) and its downstream factors KRAS and BRAF are mutated with different frequencies in non^small cell lung cancer and mutations predict clinical response to EGFR inhibitors. The present study compared the mutational status of EGFR, KRAS, and BRAF in primary tumors with the one in corresponding lymph node metastases. Experimental Design: Direct bidirectional sequencing of EGFR gene exons 18 to 21, KRAS gene codons 12/13 and 61to 68, and BRAF exon 15 was done on 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
165
3
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(184 citation statements)
references
References 41 publications
13
165
3
3
Order By: Relevance
“…However, BRAF exon 15 mutations were tested on 96 paired samples of primary lung adenocarcinomas and corresponding locoregional lymph node metastases. 133 BRAF mutations were observed in two patients with KRAS mutations demonstrating the possibility of both mutations in BRAF and KRAS occurring in the same tumor.…”
Section: Braf Mutationmentioning
confidence: 93%
See 2 more Smart Citations
“…However, BRAF exon 15 mutations were tested on 96 paired samples of primary lung adenocarcinomas and corresponding locoregional lymph node metastases. 133 BRAF mutations were observed in two patients with KRAS mutations demonstrating the possibility of both mutations in BRAF and KRAS occurring in the same tumor.…”
Section: Braf Mutationmentioning
confidence: 93%
“…It is expected that in the presence of additional molecular alterations, the effectiveness of TKI therapy for EGFR-mutant tumors will be reduced. The most frequently encountered alterations include KRAS mutations, [118][119][120][121] MET amplification, [122][123][124][125] ALK gene fusion, [126][127][128][129] PIK3CA mutations, 130 BRAF mutations, 118,[131][132][133] and IGF1R overexpression ( Figure 3). 134,135 Is EGFR mutation specific for lung adenocarcinoma?…”
Section: Other Alterations That Affect the Egfr Tki Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Five micrograms total protein for each lysate was resolved using SDS-PAGE on an 8% Bis-Tris gel (NuPAGE; Invitrogen Corp., Carlsbad, CA) using NuPAGE MOPS [3-(N-morpholino) propane sulfonic acid] SDS running buffer at 45 mA. On each gel, seven dilutions (10,25,50,125,250, 500, and 1000 ng) of recombinant intracellular domain of EGFR (recEGFR; Cell Signaling Technology, Inc., Beverly, MA) were also resolved for construction of the standard curve. Resolved protein was transferred using NuPAGE transfer buffer at 50V for 2 hours.…”
Section: Western Blot Analysis and Quantificationmentioning
confidence: 99%
“…In laboratory studies, cells with BRAF mutations were resistant to EGFR inhibitors. Previous studies had reported two novel alterations in BRAF namely an inframe deletion in exon 15 and K601L missense mutation in their study group [57].…”
Section: B-rafmentioning
confidence: 85%